Hubungan Ikan dengan Padang Lamun di Perairan Bangka Selatan, Kepulauan Bangka Belitung - Haptari, Rapita; Aisyah, Siti; Adi, Wahyu; Farhaby, Arthur M; Henri, Henri; Ferizal, Jemi; Supratman, Okto (Universitas Diponegoro, 2024)
South Bangka Regency is one of the districts that has the potential for fish biodiversity in seagrass meadows when viewed from its area and diversity. Seagrass beds are areas that have the potential to be conservation sites from an ecological point of view and represent the sustainability of fish resources. This study aims to determine the richness of fish species, fish composition, abundance, diversity, uniformity and dominating fish as well as the relationship of seagrass cover to the abundance and biomass of fish found in southern Bangka Waters. The study will be conducted in southern Bangka Regency in June 2023 covering 4 stations. Seagrass data collection in the form of seagrass cover using the quadratic transect method and swept area method (sweep) in fish data collection. The results of the study from the four stations there were 243 individuals including 23 species of fish from 18 families namely Alosidae, Apogonidae, Chaetodontidae, Engraulidae, Gerreidae, Labridae, Lethrinidae, Pinguipedidae, Platycephalidae, Scorpaenidae, Siganidae, Sphyraenidae, Syngnathidae, Terapontidae, Ambassidae, Gobiidae, Monacanthidae and Leiognathidae. The highest fish species composition was found at station 4, namely Gerres limbatus by 32.51% with 79 individuals. The abundance value found was 822 ind/ha and fish diversity was categorized as medium, fish uniformity tended to be high and dominance index was low. The abundance and biomass of fish are influenced by the percentage of seagrass cover, where the higher the percentage value of seagrass cover, the higher the abundance value and biomass of fish in the area. Kabupaten Bangka Selatan merupakan salah satu kabupaten yang memiliki potensi biodiversitas ikan di padang lamun jika dilihat dari luasan dan keanekaragamannya. Padang lamun adalah kawasan yang berpotensi sebagai tempat konservasi dilihat dari sudut pandang ekologis dan mewakili keberlanjutan sumber daya ikan. Penelitian ini bertujuan untuk mengetahui kekayaan jenis ikan, komposisi ikan, kelimpahan, keanekaragaman, keseragaman dan ikan yang mendominasi serta hubungan tutupan lamun terhadap kelimpahan dan biomassa ikan yang ditemukan di Perairan Bangka bagian selatan. Penelitian dilakukan di Kabupaten Bangka bagian selatan pada bulan Juni 2023 meliputi 4 stasiun. Pengambilan data lamun berupa tutupan lamun menggunakan metode transek kuadrat dan metode swept area (sapuan) pada pengambilan data ikan. Hasil penelitian dari keempat stasiun terdapat 243 individu mencakup 23 spesies ikan dari 18 famili yaitu Alosidae, Apogonidae, Chaetodontidae, Engraulidae, Gerreidae, Labridae, Lethrinidae, Pinguipedidae, Platycephalidae, Scorpaenidae, Siganidae, Sphyraenidae, Syngnathidae, Terapontidae, Ambassidae, Gobiidae, Monacanthidae dan Leiognathidae. Komposisi jenis ikan tertinggi terdapat pada stasiun 4 yaitu Gerres limbatus sebesar 32,51% dengan jumlah individu 79. Nilai kelimpahan yang ditemukan adalah 822 ind/ha dan keanekaragaman ikan dikategorikan sedang, keseragaman ikan cenderung tinggi dan indeks dominansi tergolong rendah. Adapun kelimpahan dan biomassa ikan dipengaruhi oleh persentase tutupan lamun, dimana semakin tinggi nilai persentase tutupan lamun maka semakin tinggi juga nilai kelimpahan dan biomassa ikan di area tersebut.